2021
DOI: 10.1155/2021/4156162
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis between Mechanical Power and Lung Ultrasound Score and Their Evaluation of Severity and Prognosis in ARDS Patients

Abstract: Background and Objective. During mechanical ventilation, the energy delivered by a ventilator to the respiratory system in one minute is defined as mechanical power (MP). It describes the combined effects of several mechanical factors, including tidal volume, driving pressure, transpulmonary pressure, flow rate, positive end-expiratory pressure, and respiratory rate on lung ventilation. As such, MP may be useful for evaluating the severity and prognosis of acute respiratory distress syndrome (ARDS), as improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 28 publications
2
13
0
3
Order By: Relevance
“…3 As a comprehensive respiratory mechanics index, MP is a quantitative measure of the energy required to overcome pulmonary resistance and maintain alveolar opening and optimal oxygenation during mechanical ventilation, and can reflect the severity of lung lesions. 34 In this study, we found that larger MP values before weaning were associated with a greater energy load that must be overcome by the respiratory muscles during spontaneous breathing, and a higher the risk of weaning failure, which is consistent with the findings of Ghiani et al 11 In accordance with previous studies, 3 35 the length of ICU stay and duration of IMV were also independent predictors of weaning failure. With a length of stay in ICU >7 days and duration of IMV >3 days, the OR values of the risk of weaning failure increased to 2.43 (95% CI: 1.96 to 3.02) and 2.33 (95% CI: 1.87 to 2.90), respectively, (both p<0.001) (table 2).…”
Section: Discussionsupporting
confidence: 92%
“…3 As a comprehensive respiratory mechanics index, MP is a quantitative measure of the energy required to overcome pulmonary resistance and maintain alveolar opening and optimal oxygenation during mechanical ventilation, and can reflect the severity of lung lesions. 34 In this study, we found that larger MP values before weaning were associated with a greater energy load that must be overcome by the respiratory muscles during spontaneous breathing, and a higher the risk of weaning failure, which is consistent with the findings of Ghiani et al 11 In accordance with previous studies, 3 35 the length of ICU stay and duration of IMV were also independent predictors of weaning failure. With a length of stay in ICU >7 days and duration of IMV >3 days, the OR values of the risk of weaning failure increased to 2.43 (95% CI: 1.96 to 3.02) and 2.33 (95% CI: 1.87 to 2.90), respectively, (both p<0.001) (table 2).…”
Section: Discussionsupporting
confidence: 92%
“…Their findings revealed that at each time point (0 h, 24 h, 48 h, and 72 h), the lung ultrasonography in the death group was higher than in the survival group (all P 0.05). Noting that although the LUS of the survivors showed a significant decline over time, that of the death group showed a significant rise over time (all P 0.05) (14) .…”
Section: Discussionmentioning
confidence: 85%
“…Overall, 13 cohort studies, including eight prospective studies [ 15 , 17 , 19 , 20 , 22 24 , 26 ] and five retrospective studies [ 14 , 16 , 18 , 21 , 25 ], were analyzed in this meta-analysis. The characteristics of the included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%